(untitled) (Research, Society and Development, 2022)
Metal alloys are the most used products in day-to-day tasks, and thousands of tons are discarded into the environment daily. By studying metal corrosion processes, it is possible to propose applications for unused metallic materials, using oxidation in an acid medium, and generating hydrogen. With this, the objective of this work is to evaluate the acid corrosion of metals, reused, for the production of hydrogen. The methodology used was corrosion carried out with steel and gray cast iron, from automotive scrap, varying and combining the metallic material, the types of acids (Sulfuric and Hydrochloric) and the reaction time, building the curve of material corrosion. To quantify Fe levels, flame atomic absorption spectrometry was used. The results showed the influence of acids and metals, with different properties and chemical compositions, on the corrosion rate and consequently on the loss of material. Based on the literature, the possible factors that are significant in the reaction that caused unexpected behaviors to occur in the results, such as the greater loss of mass of the metal when immersed in acid with lower molarity, were justified. As final considerations, it was found that it is possible to proceed with research aimed at the production of hydrogen from the corrosion of residual metals, in order to minimize environmental problems, generating a new source of energy.